Collaborative Networks in Education: Opening Spaces for another Training and Another School. - Leite-Méndez, Analía Elizabeth; Rivas-Flores, José Ignacio; Márquez-García, María Jesús; Calvo-León, Piedad; Padua Arcos, Daniela (My University, 2024)
If we metaphorically think of the school as a social and political hologram, the educational space can be seen as a reconstruction of society through the information that each school agent embodies, knows and generates (Dewey, 1938, Garcés, 2013). This idea warns us that we cannot continue to develop educational processes that do not take into account what happens outside the educational space and in turn indicates that the classroom can be a space to promote the construction of individual and collective meanings to contribute to a critical and inclusive society (Hargreaves and O'Connor, 2020). Accordingly, the focus of this communication is on the collaborative networks that are generated between schools and universities as centres of teacher education. The project is based on an assumption legitimised by different research (Penuel, et,al.,2020, Martín Barbero, 2003; Rivas, Márquez, Calvo and Martagón, 2022; Novoa, 2019) which states that the creation and development of collaborative work networks between school and university are facilitators of processes in which training, research and transfer are articulated, while at the same time allowing for the development of transformative educational actions.
Keywords: Investigación activa en educación; Profesores - Formación profesional; Collaboration; Community; Critical education; Teacher training; Citizenship